Effect of calcium formate as an accelerator on dilatancy deformation, strength and microstructure of cemented tailings backfill. (March 2022) - Wang, Yiming; Wu, Jiangyu; Pu, Hai
Abstract: Recycling mining wastes to produce cemented tailings backfill (CTB) is the optimal approach to eliminate the environmental pollution caused by their accumulation. However, its low strength limits its application. Using calcium formate (CF) as an accelerator for improving its mechanical properties is of great significance to promote sustainable development. The effects of CF dosage and curing time on dilatancy deformation, compressive strength and microstructure of CTB were investigated through mechanical compression, scanning electron microscope (SEM) and energy dispersive spectrometer (EDS) tests. The strengthening and deterioration mechanisms of CF dosage on CTB were revealed, and its engineering practicability was systematically evaluated. The results show that the variation of volumetric strain in the dilatancy deformation stage firstly increase and then decrease with the increases of CF dosage and curing time. The relationship between CF dosage and compressive strength can be characterized by quadratic polynomial, and the optimal CF dosage characterizing the superior mechanical property of CTB is between 1.60 and 1.84. The supplement of CF reduces the size and distribution of microcracks and micropores, thereby optimizing the microstructure of CTB. Nevertheless, the excessive dosages of CF deteriorate the microstructure of CTB and produce serious defects, which cannot be effectively filled by hydration products, thus weakening the strength property of CTB. This study provides an effective accelerator for improving the mechanical properties of CTB, which is of great significance to promote the recycling of tailings. Graphical abstract: Image 1 Highlights: CF as accelerator reinforces CTB for recycling tailings. CF effects on dilatancy deformation, strength and microstructure of CTB. Coupling effects of CF dosage and curing time on strength of CTB. Relation between microstructure and dilatancy deformation of CTB.